Cultural relations between India and Uzbekistan - Mourya, Rajesh; Garima Diwan (RADINKA JAYA UTAMA PUBLISHER, 2024)
The study of cultural relations between India and Uzbekistan particularly focuses on their historical, cultural and commercial relations. It studies the evolution of the valuable historical ties between the two countries, which have occurred through dialogue between the Indian subcontinent and the Central Asian region. Furthermore, cultural exchange, art, literature, and trade characteristics of Indian and Uzbek culture are also secondary in this study. This study helps in understanding all the aspects through which relations have evolved between the two countries and how they continue to learn from each other.